SISTEM PENDUKUNG KEPUTUSAN PENANGANAN PASIEN UGD MENGGUNAKAN METODE FUZZY MULTIPLE ATTRIBUTE DECISION MAKING DENGAN SIMPLE ADDITIVE WEIGHTING PADA PUSKESMAS GAJAHAN SURAKARTA - Riza Riza; Muhammad Hasbi; Iwan Ady Prabowo (STMIK Sinar Nusantara, 2018)
In the Public Health Center, the handling of patients of the Emergency Unit is classified as not much happening because now many hospitals are ready to handle all forms of patient complaints. At the Public Health Center, the handling of patients in the Emergency Unit occurs only for mild illness and with outpatient treatment. To decide the condition of the patient should be treated in the room or should be referred to what hospital, the Center for Public Health has not been able to determine it so that for regular referrals addressed directly to a fully equipped hospital. The number of hospital types and the poor condition of the patient makes the decision making must be clear and appropriate to the actual patient condition. To overcome these problems, the authors make an application decision system with FMADM SAW method to determine where the patient should be handled further, surgery, ICU, road or hospitalization, a referral must be in accordance with the condition of the patient. The method used in the form of data analysis methods in the form of data collection techniques, data types, and system design. This application also has advantages in making report analysis results that can be done quickly and easily. To facilitate the implementation of the system, the authors limit the problem only on the problem of determining the purpose of treatment alone. The system that the author designed the decision-making system with FMADM SAW method. The result of analysis and design in the form of decision support system of patient handling of new Emergency Unit with computer-based and application of FMADM SAW method. The tested system will produce patient data information and result of decision support process of patient handling. From another process is given a form of separate data collection process according to the needs of the process of supporting patient handling decisions and considered feasible if the process is stored completely. It is hoped that this system can assist the Public Health Center admin in dealing with Emergency Room patients.Keywords: Decision Support System, Emergency Room, FMADM (SAW), Public Health Center